Dwaj zawodnicy, ring, krematorium – sprawa nie jest prosta, czyli o prawdzie i fikcji w sportowych narracjach o Zagładzie (na przykładzie opowiadania Bokser i śmierć) - Wolski, Paweł (Załącznik Kulturoznawczy, 2022)
The author traces the biography of Józef Hen in connection with his sporting experiences and reflects upon the extent to which one should consider him an author of Polish sports literary writing. He then takes a deeper insight into one of his three short stories on sports, namely Boxing and Death in order to establish the factual reference of the fictional tale and, in particular, its protagonists. This leads him to the conclusion that a sports narrative which involves any given aspect or event related to the Holocaust constitutes an autonomous genre, different from both Holocaust and sports narratives as such.